Jack’s Anxieties and Defense Mechanisms in Fight Club - E.O. Sanusi (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
In this article, I want to analyze a movie entitled Fight Club by David Fincher. It is one of Film Noir movies that is adapted from Chuck Palahniuk’s novel. Film Noir usually employs mentally unstable characters. In this movie, Jack, the main character, has psychological problems which causes his anxieties. Thus, I want to find out the types of Jack’s anxiety and the defense mechanism he uses to cope with it. I will identify the types of Jack’s anxieties and the defense mechanisms he uses. His anxieties have led him to have insomnia, depression, and the formation of his alter ego Tyler Durden. They also cause his problematic behavior that results in the destruction of his life. In order to cope with his psychological problem, Jack uses several defense mechanisms. In my analysis, I use theory of anxieties and defense mechanisms by Sigmund Freud. Based on the analysis, I find that Jack has reality anxiety, neurotic anxiety, and moral anxiety. To cope with anxieties, he uses defense mechanisms such as repression, fixation, and regression. His anxieties and unhealthy defense mechanisms are what have driven him to have problematic behavior.  Keywords: anxiety, defense mechanism, neurotic anxiety, reality anxiety, moral anxiety